With Mortal Voice : The Creation of Paradise Lost - Shawcross, John T. (Book collections on Project MUSE., 1982)
More often than not, critics have looked upon Milton's great epic not as a literary work but rather as a theological tract or a display of Renaissance learning. In this book John Shawcross seeks to redress that critical imbalance by examining the poem for its literary values. In doing so he reveals the scope and depth of Milton's poetic craftsmanship in his control of such elements as structure, myth, style, and language; and he offers new approaches to reading Paradise Lost as a literary masterpiece rather than a relic of religious history.